PECULIARITIES OF AUTONOMOUS REGULATION IN THE PATIENTS WITH SYNCOPE LIVING IN AN INDUSTRIAL CITY - Илья Дмитриевич Мартынов; Арнольд Наумович Флейшман (Медицина в Кузбассе, 2017)
Subject. Changes in heart rate variability and systemic hemodynamics in orthostasis in the patients with neurogenic syncope living in an industrial city.